Traditional and Western Buddhism in Russia: a comparative study - Mongush, Marina V. (The New Research of Tuva, 2016)
The article examines the history of the arrival and spread of Buddhism, including the versions that came from the West in late 20th century, in the regions of Russia where indigenous population have traditionally followed the Mahāyāna – the northern, i.e. Tibetan version of Buddhism (Kalmykia, Buryatia, Tuva, Zabaikalski Krai (Transbaikalia) and Irkutsk Oblast).Being followers of the Mahāyāna, most Russian Buddhists largely belong to the Gelug school, with a certain number of followers of other schools of Tibetan Buddhism – Karma Kagyu, Nyingma and Sakya. The overall number of practicing Buddhists in Russia does not exceed 500,000. There are about 900,000 ‘Ethnic Buddhists’ in Buryatia, Kalmykia and Tuva. The organizational structure and doctrine of Buryat, Mongol and Kalmyk Buddhism is akin to those in Mongolian Buddhism.Besides developing its own traditional Buddhism, since the 1990s Russia has been influenced by a different version of this religion – a Buddhism adapted to Western mentality and lifestyle. Western-style Buddhist communities typically contrast themselves to traditional Kalmyk, Buryat and Tuvan communities and present their lifestyles as the only appropriate ones for European Russians. Although they claim possessing a direct religious and dogmatic link between their teachings and Tibetan Buddhism, in fact those are their own versions of Buddhism.At the moment in European Russia there are about 200 independent Buddhist communities and organizations of Western-style Buddhism. They are largely concentrated in Russia’s biggest cities – Moscow, St. Petersburg, Novosibirsk, etc. The most active of them is the “International Association of Karma Kagyu School Buddhists”, registered in 1993. Religious studies scholars classify it as a Neo-Buddhist cult adapted to the religious needs of its followers to provide fast access to ‘efficient’ and ‘occult’ Tibetan ritual practices. The same path has been chosen by the Association of Dzogchen Communities and the Rimei Community (both have beeт active in St. Petersburg since 1989-1991).The revival of Buddhism as one of Russia’s religions goes beyond the rebuilding of the old temples and the construction of new ones in Buddhism’s traditional domain. The process is augmented by the rise of the communities which popularize new models of religious life adapted from the West without any specific Tibetan Buddhist historical and cultural prototypes.
Keywords: traditional Buddhism; Tibetan Buddhism; Western Buddhism; Buddhist communities; Russian Buddhism; Neo-Buddhism